Integrated Physics E-Booklet Model of Tsunami Disaster Mitigation in Outer Islands of The West Coast Sumatra for High School Level - Fitri, Elsi Adelia; Johan, Henny; Karyadi, Bhakti; Sudirman, Sudirman; Putriani, Eli (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2024)
Indonesia is a country located at the confluence of the Indo-Australian and Eurasian plates, which collide with each other, one of which is off the west coast of the island of Sumatra. This situation carries a significant risk of triggering a tsunami disaster. To minimize these risks, it is necessary to provide disaster awareness to all groups, especially students. This study aims to produce an e-booklet on integrated wave material for tsunami disaster mitigation on the outermost islands of Sumatra's west coast. The study employs a research and development methodology. The research instruments were questionnaires, interview guides, validation sheets, and questions. We conducted descriptive, quantitative, and qualitative data analysis. The research results led to the production of an integrated e-booklet for tsunami disaster mitigation, tailored to the region's potential in mitigation efforts. The level of disaster preparedness after using the e-booklet is included in the high preparedness category. The relationship between knowledge and level of disaster preparedness is linear. So that this e-booklet can be used as teaching material to provide disaster preparedness on the outermost islands of the west coast of Sumatra.